Structure evolution during film blowing: An experimental study using in-situ small angle X-ray scattering. (January 2016) - Troisi, E.M.; van Drongelen, M.; Caelers, H.J.M.; Portale, G.; Peters, G.W.M.
Graphical abstract: Highlights: Unique in-situ SAXS study during film blowing of a series of LLDPE performed. Effect of processing conditions and material on morphological features investigated. BUR influences crystallinity and lamellar thickness evolution, TUR orientation. Crystallinity increases of 50% above frost line due to secondary crystallization. Validation of the on-line study using ex-situ WAXD/SAXS. Abstract: The on-line morphological development during film blowing of 2 different linear low density polyethylenes (LLDPEs) and a blend of LLDPE with low density polyethylene (LDPE) has been investigated, for the first time, using synchrotron Small Angle X-ray Scattering (SAXS). The processing conditions, blow-up ratio and take-up ratio, have been varied and the resulting lamellar thickness, linear crystallinity and orientation evolution in machine direction is obtained from a detailed analysis of SAXS data. Ex-situ SAXS and wide angle X-ray Diffraction (WAXD) confirmed the effect of molecular structure and composition on structure evolution observed in the on-line experiments. The results obtained provide a valuable set of data for the understanding of the film blowing process and can be used to extend and improve numerical model.